Silica Aerogel Composites Novel Fabrication Methods - Sachithanadam, Mahesh; Joshi, Sunil Chandrakant; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book explores the improvement in thermal insulation properties of protein-based silica aerogel composites fabricated by a novel, inexpensive and feasible method. The resulting material exhibits polymeric foam behavior including high compressibility, super-hydrophobic qualities and excellent strain recovery in addition to low thermal conductivity. The fabrication methodologies are explained in great detail and represented in flowcharts for easy reference and understanding. This monograph gives readers a new perspective on composite fabrication using methods other than the traditional ones and explores the endless ways of altering the composition to modify the properties of the silica aerogel composites. Applications for this novel composite are diverse and range from those in the pharmaceutical and aerospace industries to the oil and gas industries.
Aerogels Today and Market Outlook -- Fabrication of Novel Silica Aerogel Composites -- Brittle to Ductile Transition in Aerogel Composites -- Mechanical Properties of Aerogel Composites -- Thermal Performance of Aerogel Composites -- Magnetic Properties of Aerogel Composites -- Conclusions and Futuristic Applications -- Appendix for MATLAB Codes.
Keywords: Ceramic materials; Materials; Polymers; Ceramics; Materials Engineering; Polymers